A Brief Overview and History of Human Nutrition and Health - Ahsan, Haseeb (Current Biochemistry, 2022)
Nutritional biochemistry is finally getting the attention it deserves, despite the fact that food and nutrition have been studied for centuries. In 1926, less than 100 years ago, the first vitamin was extracted and chemically characterized, leading to studies on single-nutrient deficiency diseases. Nutritional research on chronic diseases like cardiovascular disease, diabetes, obesity, and malignancies has hastened in the past few decades, especially after the year 2000. Nutrition has played a key role in the improvement of public health since the past 200 years, and is expected to play a major role in public health for the future. Keywords: nutrition, diet, history, food, agriculture.